The Growth Aftermath of Natural Disasters - Fomby, Thomas; Ikeda, Yuki; Loayza, Norman (2012)
This paper provides a description of the macroeconomic aftermath of natural disasters. It traces the yearly response of gross domestic product growth - both aggregated and disaggregated into its agricultural and non-agricultural components - to four types of natural disasters - droughts, floods, earthquakes, and storms. The paper uses a methodological approach based on pooling the experiences of various countries over time. It consists of vector auto-regressions in the presence of endogenous variables and exogenous shocks (VARX), applied to a panel of cross-country and time-series data. The analysis finds heterogeneous effects on a variety of dimensions. First, the effects of natural disasters are stronger, for better or worse, on developing than on rich countries. Second, while the impact of some natural disasters can be beneficial when they are of moderate intensity, severe disasters never have positive effects. Third, not all natural disasters are alike in terms of the growth response they induce, and, perhaps surprisingly, some can entail benefits regarding economic growth. Thus, droughts have a negative effect on both agricultural and non-agricultural growth. In contrast, floods tend to have a positive effect on economic growth in both major sectors. Earthquakes have a negative effect on agricultural growth but a positive one on non-agricultural growth. Storms tend to have a negative effect on gross domestic product growth but the effect is short-lived and small. Future research should concentrate on exploring the mechanisms behind these heterogeneous impacts.